A survey of theological seminary libraries in the greater Manila area - Simarangkir, Tunggul P. (Institute of Library Science, University of the Philippines Diliman, 1971)
This is a survey of seven Theological Seminary Libraries in the Greater Manila Area for the school year 1969-1970. The study includes all aspects of the seminary libraries, such as objectives of the seminary and its library, administrative organization, collection, technical services, personnel, library use, library building and equipment.